Managing innovation driven companies : approaches in practice - Tschirky, Hugo , 1938- (Palgrave Macmillan, 2011)
This book emphasizes the practical side of Technology and Innovation Management. It includes significant contribution to the practice of strategizing, management of competences and innovation management. The findings presented on these selected topics are research-based, however each contribution covers the implementation of the research results